2019
DOI: 10.1084/jem.20190009
|View full text |Cite
|
Sign up to set email alerts
|

C3- and CR3-dependent microglial clearance protects photoreceptors in retinitis pigmentosa

Abstract: Complement activation has been implicated as contributing to neurodegeneration in retinal and brain pathologies, but its role in retinitis pigmentosa (RP), an inherited and largely incurable photoreceptor degenerative disease, is unclear. We found that multiple complement components were markedly up-regulated in retinas with human RP and the rd10 mouse model, coinciding spatiotemporally with photoreceptor degeneration, with increased C3 expression and activation localizing to activated retinal microglia. Genet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 71 publications
(99 reference statements)
3
69
0
Order By: Relevance
“…The introduction of cytokines IL-6, IFNγ or TNFα to microglial cultures promotes the synthesis of complement components [ 122 ]. Increased C3 expression was observed in infiltrating microglia in the outer nuclear layer of rd10 mice along with opsonisation of degenerating photoreceptors by C3b [ 124 ]. Interestingly, this study also showed that genetic ablation of C3 or the C3 receptor (CR3) accelerated photoreceptor degeneration.…”
Section: Recruitment and Activation Of Microglia And Monocytesmentioning
confidence: 99%
“…The introduction of cytokines IL-6, IFNγ or TNFα to microglial cultures promotes the synthesis of complement components [ 122 ]. Increased C3 expression was observed in infiltrating microglia in the outer nuclear layer of rd10 mice along with opsonisation of degenerating photoreceptors by C3b [ 124 ]. Interestingly, this study also showed that genetic ablation of C3 or the C3 receptor (CR3) accelerated photoreceptor degeneration.…”
Section: Recruitment and Activation Of Microglia And Monocytesmentioning
confidence: 99%
“…In our comprehensive analyses, we furthermore detected a considerable number of genes encoding for components of the complement system that is part of the innate immune system. Various complement factors have been reported to be upregulated in retinae of human patients suffering from RP or in retinae of mice following genetically or light-induced photoreceptor degeneration in mice (47)(48)(49)(51)(52)(53)(54). Activation of the complement system promotes microglia/in ltrative macrophages migration and eventually complement activated lysis (48,51).…”
Section: Discussionmentioning
confidence: 99%
“…Still, con icting data exist regarding the exact role of complement system activation and its impact on photoreceptor degeneration. Mice with a de ciency in complement factor D are protected from light-induced photoreceptor degeneration (47), indicating a detrimental role for photoreceptor survival, but the de ciency in complement component 3 (C3) or complement receptor 3 (CR3) in a genetic mouse model of photoreceptor degeneration increases microglia-mediated neurotoxicity to photoreceptors (54). Thus, the detailed function of the complement system and its speci c role in microglia and Müller cells and its contribution to photoreceptor degeneration has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, dying or stressed photoreceptors were the object of phagocytosis, in a manner mediated by complement component 3 (C3) and its receptor CR3. 32 Moreover, inhibition of microglia phagocytosis was associated with preservation of rod photoreceptors. 31 In summary, over the last 15 years, there has been a dramatic increase in our knowledge of the role of microglia in regulating normal health of the nervous system including the retina.…”
Section: Resident Microglia As Guardians Of the Retinamentioning
confidence: 99%
“…TUNEL positive photoreceptors). Rather, dying or stressed photoreceptors were the object of phagocytosis, in a manner mediated by complement component 3 (C3) and its receptor CR3 . Moreover, inhibition of microglia phagocytosis was associated with preservation of rod photoreceptors …”
Section: Resident Microglia As Guardians Of the Retinamentioning
confidence: 99%